A Test of the Catering Theory of Dividends: Empirical Evidence from an Emerging Economy India - Nishant B. Labhane (Asian Academy of Management Journal of Accounting and Finance, 2019)
The present study examines the catering theory of dividends proposed by M. Baker and J. Wurgler in 2004 for 781 sample firms listed on National Stock Exchange (NSE) in India during 1994–1995 to 2014–2015. The dividend premium, a proxy to measure the time-varying investors’ desire for dividends, is captured in each year during the study period. The dividend premium is negative for most of the years of the study period which is consistent with the previous research studies in the U.S. The results for the relationship between the dividend payment variables and the investors’ demand for dividend indicate that when the dividend premium is high the non-dividend paying firms initiate dividend payment in the following year whereas, when the dividend appear at the stock market dividend discount the dividend-paying firms omit (not continue) paying dividend in the subsequent year. The empirical results suggest that the decision to initiate and continue dividend payment have strong predictive power for the future excess share returns of dividend-paying firms over non-dividend paying firms. Thus, our results support the notion that the managers of Indian firms cater rationally to investors demand for dividends by paying dividends when investors place a premium on dividend-paying firms and vice versa.